Nouvelles techniques de dessalement des eaux de mer, cas d’études : Dessalement des eaux de mer dans la Wilaya de Mostaganem - KELLAL, Safia Ferdous (My University, 2023)
The research explores recent advancements in the field of water desalination, a critical element in addressing the growing demand for fresh water on a global scale. With dwindling freshwater resources, it becomes imperative to explore more efficient and environmentallyrespectful approaches to produce potable water from seawater or brackish water. The study then focuses on emerging modern desalination techniques, including enhanced reverse osmosis through the use of innovative membranes, low-energy consumption desalination processes like electrodialysis, and multi-effect thermal desalination technologies. Each of these approaches is examined in detail, emphasizing their advantages, limitations, and potential for large-scale implementation. Sustainability is at the core of this study, exploring the environmental and economic implications of these new desalination techniques. It also delves into progress in the valorization of by-products from desalination, contributing to minimizing the impact on local ecosystems.
Keywords: water; desalination; reverse osmosis; physic-chemical quality; portability